Peran Social Media Influencer dalam Menciptakan Product Value Sebagai Pendorong Green Lifestyle Sustainbility - Rifai Apriture Afianto; Dati Putra Nur Akhmad; Nur Fitriani Nikmatussholekha (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This research examines the role of social media influencers in shaping product values ​​that encourage a sustainable green lifestyle. With increasing attention to environmental issues, social media influencers have significant potential in influencing consumer behavior through the promotion of environmentally friendly products. A quantitative approach was used to collect data through an online questionnaire. A total of 190 samples were analyzed using Structural Equation Modeling (SEM) with Smart PLS. Participants in this research were selected using a purposive sampling approach based on certain criteria such as having experience purchasing environmentally friendly products. The research results show that social media influencers and product value have a significant effect on Sustainable Green. In addition, influencers play a role in educating consumers about the environmental and social benefits of the product, which in turn increases the value of the product in the eyes of consumers. By promoting products that support sustainability, influencers help encourage the adoption of green lifestyles among the wider community. This research concludes that strategic collaboration between brands and influencers is critical to creating strong product value and contributing to global sustainability efforts.